Review: Disposable Duodenoscopes in the Era of Climate Change—A Global Perspective - Darak, Harish; Giri, Suprabhat; Sundaram, Sridhar (Journal of Gastrointestinal Infections, 2022)
Endoscopic retrograde cholangiopancreatography remains a major interventional procedure in gastroenterology clinical practice. There have been concerns of hospital related infections secondary to the reusable duodenoscopes despite optimal strategies for high-level disinfection. While there are have been potential changes in duodenoscope design with availability of disposable caps, the increased risk of infection has led to the advent of single-use duodenoscopes in clinical practice. This innovation may help reduce infections due to duodenoscope reprocessing, while ensuring optimal performance similar to reusable duodenoscopes. However, their impact on the environment and overall carbon footprint has not been discussed. Moreover, disposable duodenoscopes are costly equipments. In developing countries with low income and poor insurance coverage, the clinical utility of this equipment is yet to be ascertained. With major push for Go-Green initiatives by various governments, there has to be clarity on not just use but also disposal and recycling of disposable duodenoscopes. In this narrative review, we discuss the role of disposable duodenoscopes in clinical practice in this era of climate change from the Indian perspective.
Keywords: climate change; environment; equipment reuse; New Delhi metallo-betalactamase; sustainability